1975
DOI: 10.1097/00000658-197510000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystokinin Metabolism in Man and Dogs

Abstract: We have developed a sensitive, specific and reproducible radioimmunoassay for cholecystokinin (CCK) with which basal levels of CCK of between 400-800 pg/ml have been measured in normal man, in patients with diabetes and with duodenal ulcer disease, and in normal dogs. After a meal, circulating levels of CCK rose to 1000-1200 pg/ml in human subjects. Release of CCK was more rapid in diabetic and duodenal ulcer patients than in normal subjects, but elevated postprandial levels persisted much longer in normal sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
1
2

Year Published

1984
1984
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(39 citation statements)
references
References 19 publications
1
35
1
2
Order By: Relevance
“…The serum CCK then promptly returns to baseline due to its rapid metabolism (2.5 minutes serum halftime) [19]. The occurrence of a maximum gallbladder contraction difference of 21% (GBCI10 -GBCI 5) and a decline afterwards is in one accord with this reported 2.5 minute serum half-life of serum CCK.…”
Section: Discussionsupporting
confidence: 64%
“…The serum CCK then promptly returns to baseline due to its rapid metabolism (2.5 minutes serum halftime) [19]. The occurrence of a maximum gallbladder contraction difference of 21% (GBCI10 -GBCI 5) and a decline afterwards is in one accord with this reported 2.5 minute serum half-life of serum CCK.…”
Section: Discussionsupporting
confidence: 64%
“…The results suggest that increased plasma CCK concentrations observed after meal stimulation and during bombesin infusion are not the result of impaired metabolism of CCK by loxiglumide. It has previously been shown that circulating peptides like CCK are rapidly metabolised in capillaries throughout the body (Strunz et al, 1978), especially in the kidney (Thompson et al, 1975). However, small molecular forms of CCK are also extracted effectively by the liver (Sakamoto et al, 1985).…”
Section: Resultsmentioning
confidence: 99%
“…This hormone has a very short half-life in the circulation, measured in minutes. 30 This is also the ideal time to stimulate a satiety response when it would be able to limit the size of the meal ingested. Because of the short duration of action of CCK when the physiological hormone needs to be active, accentuation of that response might increase appetite suppression, while not being overly stimulatory and certainly not acting over a longer duration of time that might be associated with trophic effects.…”
Section: Allosteric Modulation Of Receptorsmentioning
confidence: 99%